Enhancing Disaster Preparedness among Elementary School Students through Flood Preparedness Training: A Pre-Experimental Study - Hermalinda Herman; Yanti Pupita Sari; Sovia Susianty; Ira Mulya Sari (Fakultas Keperawatan Universitas Andalas, 2025)
Children are a vulnerable group in disasters due to their limited physical strength, susceptibility to illness, and emotional instability. Reducing vulnerability is essential for protecting children during disasters, and one crucial factor in their preparedness is disaster education. This study aimed to evaluate the effect of flood disaster preparedness training on improving elementary school students’ preparedness in dealing with flash floods. A pre-experimental design with a one-group pretest–posttest approach was employed, involving 50 students from SDN 23 Guguak Randah. The intervention consisted of a 60-minute training session using lectures, discussions, videos, and disaster simulations. Disaster education plays a significant role in raising children's awareness about disasters and their risk perception. Students’ knowledge was assessed using a validated 10-item questionnaire before and after the intervention. The data were analyzed using the Wilcoxon test. The results showed an increase in the mean knowledge score from 69.20 (SD = 17.71) before training to 80.40 (SD = 15.53) after training (z = 4.089, p < .0001). These findings demonstrate that flood preparedness training significantly enhances students’ knowledge and awareness of disaster preparedness. Disaster education programs for children have been considered an innovative approach to disaster risk reduction The use of lecture-based methods, complemented by simulations, can significantly improve students' comprehension of the concepts and materials being taught. Routine implementation of disaster preparedness programs in schools, in collaboration with the Regional Disaster Management Agency (BPBD), is recommended to strengthen children’s resilience and readiness for future disasters.